The Effect of Corporate Performance and Corporate Governance on Manufacturing Company Carbon Emission Disclosure - Ryan Bagas Wikantyoso; Robiyanto Robiyanto; Budi Frensidy (Indonesian Journal of Sustainability Accounting and Management, 2024)
The aim of this study is to examine the effect of company performance and corporate governance on the disclosure of carbon emissions of manufacturing companies. This study uses secondary data in the form of financial reports and sustainability reports from manufacturing companies that have been listed on the Indonesia Stock Exchange (IDX) for the period 2015 -2022. The data collection technique used a purposive sampling method with a sample of 93 companies. Data analyzed by using panel regression method. The results of this study show that company performance variables have a significant positive effect on disclosure of carbon emissions, but corporate governance variables do not have a significant negative effect on carbon emissions. The study suggests corporate governance will reduce the company's carbon emission levels. Hence, it is very important to enhance the company’s corporate governance practices beyond the mandatory matters. This study is one among few studies which have been conducted in Indonesia to examine company performance and corporate governance regarding carbon emissions in the manufacturing industry in Indonesia. This study focuses on examining the manufacturing industry in Indonesia and this research has different results and points of view from previous researches.